2014
DOI: 10.3390/ma7064803
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and Characterization of Ti6Al4V Lattice Components Manufactured by Selective Laser Melting

Abstract: The paper investigates the fabrication of Selective Laser Melting (SLM) titanium alloy Ti6Al4V micro-lattice structures for the production of lightweight components. Specifically, the pillar textile unit cell is used as base lattice structure and alternative lattice topologies including reinforcing vertical bars are also considered. Detailed characterizations of dimensional accuracy, surface roughness, and micro-hardness are performed. In addition, compression tests are carried out in order to evaluate the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 40 publications
(56 reference statements)
2
49
0
Order By: Relevance
“…The structure is uniformly built and aligned parallel to the building direction ( Figure 14) in the 0 • orientation. The values determined for hardness correlate to values found in the literature [38,46,47]. By Song et al [13] was shown that mechanical properties depend on the processing parameters.…”
Section: Vickers Hardnesssupporting
confidence: 72%
“…The structure is uniformly built and aligned parallel to the building direction ( Figure 14) in the 0 • orientation. The values determined for hardness correlate to values found in the literature [38,46,47]. By Song et al [13] was shown that mechanical properties depend on the processing parameters.…”
Section: Vickers Hardnesssupporting
confidence: 72%
“…15 Therefore, understanding how the AM process influences the part microstructure is of paramount importance. In this regard, the focus of this work will be on electron beam melting (EBM) and selective laser melting (SLM), which are among the main AM processes for Ti6Al4V.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization of process parameters, in order to obtain almost full density and good mechanical properties of the bulk materials, represented the first step of the development of the SLM technology and of the scientific production [2][3][4], but research in producing parts with customized porosity and higher performances is raising [5,6]. Porous materials are exploited in different sectors, ranging from biomedical to aerospace [7,8].…”
Section: Introductionmentioning
confidence: 99%